Inspiratory Constraints and Ventilatory Inefficiency Are Superior to Breathing Reserve in the Assessment of Exertional Dyspnea in COPD. (4th March 2019) - Neder, J. Alberto; Berton, Danilo C.; Marillier, Mathieu; Bernard, Anne-Catherine; O'Donnell, Denis E.; ,
Abstract: Combining measurements of impaired lung mechanics (inspiratory constraints) with an index of increased respiratory stimuli to metabolic demand (poor ventilatory efficiency) might enhance the ability of cardiopulmonary exercise testing (CPET) in exposing a mechanistic role for ventilation on exertional dyspnea in COPD. In addition to the standard approach to suggest ventilatory limitation to exercise – a low breathing reserve (1−(peak ventilation (V̇E)/maximal voluntary ventilation × 100 < 20%) – we assessed the presence of critical inspiratory constraints (end-inspiratory lung volume (EILV)/total lung capacity (TLC) ≥ 0.9) and ventilatory inefficiency (V̇E/CO2 output (V̇CO2 ) nadir > 34) in 288 patients with mild to very severe COPD (FEV1 ranging from 18 to 121% predicted). We found that ∼50% of the patients with preserved breathing reserve developed critical inspiratory constraints. A low breathing reserve was weakly related to a lower peak O2 uptake (V̇O2 ) and/or a higher dyspnea burden; for instance, patients with low breathing reserve but without critical inspiratory constraints had similar dyspnea and peak V̇O2 than those with preserved breathing reserve ( p  > 0.05). In contrast, critical inspiratory constraints and ventilatory inefficiency were strongly associated with a negative outcome (likelihood ratio = 42.3 and 47.7, respectively; p  < 0.001). A multiple logistic regression analysis revealed that only EILV/TLC ≥ 0.9 and V̇E/V̇CO2 nadir >34 predicted a severely reduced peak V̇O2 due to a high dyspnea burden ( p  < 0.001). Measurements of dynamic mechanical constraints and ventilatory inefficiency during incremental CPET are key to determine the impact of COPD on dyspnea and exercise tolerance across the spectrum of disease severity.